Penunjukan Kepala Otorita Ibu Kota Nusantara Menurut Undang-Undang Nomor 3 Tahun 2022 - Siti Nur Aisyah; Ni’matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2024)
This study aims to analyze President’s prerogatif rights in election of the head of Nusantara Capital City Authority and the implication to the head of Nusantara Capital City Authority’s position and authority. This study contain two research problem formulation: Is the election of the head of Nusantara Capital City Authority using President’s prerogative right? What the implication to the head of Nusantara Capital City Authority’s position and authority? This is a normative judicial research. Legal materials used in this study collected by literature review and document review method, and written descriptively. This study used qualitative-descriptive method conducted using legislation approach. This study concluded the election of the head of Nusantara Capital City Authority is a President’s prerogative right. Second, it’s in equal position with the minister. The authority came from Government Regulations and President Regulations, Nusantara Capital City Authority have no autonomous authority. This study offers to return “after having a consult” into “with approval” or “with consideration”. It’s better to separate the preparation and translocation institution, and regional administrators institution to carry out autonomous authority well and return last government model and giving special authority as a special area of ​​the capital, also bringing back Regional Legislative Council.